Coordination framework of cadmium(II), harvested from dithiolate-imidazole binary ligand systems: Crystal structure, Hirshfeld surface analysis, antibacterial, and DNA cleavage potential. (1st December 2020) - Adhikari, Suman; Bhattacharjee, Tirtha; Gupta, Raj; Daniliuc, Constantin-Gabriel; Montazerozohori, M.; Naghiha, R.; Masoudiasl, A.
Graphical abstract: The novel one-dimensional coordination polymer with binuclear building node [Cd2 (i-mnt)2 (Im)2 ]DMF2 n (1 ) harvested from 1, 1-dicyanoethylene-2, 2-dithiolate ( i-mnt 2− ) and imidazole ( Im ) has been systemically designed, synthesized and structurally characterized by elemental analysis, FT-IR and 1 H NMR spectroscopy. Single crystal X-ray diffraction analysis revealed that in 1, each Cd(II) is in penta-coordinated environment having slightly distorted square pyramidal geometry (τ5 = 0.24) and have two bridging thiolate ends of i-mnt −2 along with one DMF solvent molecule. The flexible i-mnt 2− ligand acts as a tridentate connector by ligating with Cd(II) centers in parallel dimeric units forming a 1D polymeric chain. Hirshfeld surface analyses and two dimensional (2D) finger print plots were employed to decode all types of non-covalent contacts in the crystal frameworks, allowing a systematic evaluation of the crystal structure. From HS analysis, it was observed that N⋯H/H⋯N type interactions (22.1%) have the major contribution compared to overall non-covalent interacrtions. The share of H⋯O/O⋯H interactions of the total surface is only 3.7%, their role is important in the direction and organization of crystal packaging. The in-vitro antimicrobial study of 1 against Gram-positive ( Staphylococcus aureus and Bacillus subtilis ) and Gram-negative ( E. coli and P. aeruginosa ) human pathogenic bacterial strains show promising antimicrobial activities. Furthermore, DNA cleavage study ( E. coli DNA) of 1 using gel electrophoresis method revealed promising DNA cleaver property similar to H2 O2 due to the efficient coordination of Cd(II) ion. Highlights: The novel one-dimensional coordination polymer with binuclear building node [Cd2 (i-mnt)2 (Im)2 ]DMF2 n (1 ) harvested from 1, 1-dicyanoethylene-2, 2-dithiolate ( i-mnt 2− ) and imidazole ( Im ) has been structurally characterized. Each Cd(II) is in penta-coordinated environment having slightly distorted square pyramidal geometry (τ5 = 0.24). Hirshfeld surface analysis demonstrates the essential role of NH⋯O interactions in the directionality and organization of the crystal packing. The in-vitro antimicrobial study of 1 against Gram-positive ( Staphylococcus aureus and Bacillus subtilis ) and Gram-negative ( E. coli and P. aeruginosa ) human pathogenic bacterial strains show promising antimicrobial activities. DNA cleavage study ( E. coli DNA) of 1 using gel electrophoresis method revealed promising DNA cleaver property similar to H2 O2 due to the efficient coordination of Cd(II) ion. Abstract: The novel one-dimensional coordination polymer with binuclear building node [Cd2 (i-mnt)2 (Im)2 ]DMF2 n (1 ) harvested from 1, 1-dicyanoethylene-2, 2-dithiolate ( i-mnt 2− ) and imidazole ( Im ) has been systemically designed, synthesized and structurally characterized by elemental analysis, FT-IR and 1 H NMR spectroscopy. Single crystal X-ray diffraction analysis revealed that in 1, each Cd(II) is in penta-coordinated environment having slightly distorted square pyramidal geometry (τ5 = 0.24) and have two bridging thiolate ends of i-mnt −2 - along with one DMF solvent molecule. The flexible i-mnt 2− ligand acts as a tridentate connector by ligating with Cd(II) centers in parallel dimeric units forming a 1D polymeric chain. Hirshfeld surface analyses and two dimensional (2D) finger print plots were employed to decode all types of non-covalent contacts in the crystal frameworks, allowing a systematic evaluation of the crystal structure. From HS analysis, it was observed that N⋯H/H⋯N type interactions (22.1%) have the major contribution compared to overall non-covalent interacrtions. The share of H⋯O/O⋯H interactions of the total surface is only 3.7%, their role is important in the direction and organization of crystal packaging. The in-vitro antimicrobial study of 1 against Gram-positive ( Staphylococcus aureus and Bacillus subtilis ) and Gram-negative ( E. coli and P. aeruginosa ) human pathogenic bacterial strains show promising antimicrobial activities. Furthermore, DNA cleavage study ( E. coli DNA) of 1 using gel electrophoresis method revealed promising DNA cleaver property similar to H2 O2 due to the efficient coordination of Cd(II) ion.